Stable Radicals with Protective Umbrellas Integrated on the Surface of 2D Layered Materials. (22nd July 2021) - Chen, Yuanyuan; Peng, Jian; Sheng, Tian; Qin, Ruixuan; Dai, Shuqi; Shi, Zaifa; Tang, Zichao; Wang, Laisen; Zhang, Qinghua; Han, Bin; Sun, Liping; Xu, Jun; et al.
Abstract: Radicals are closely related to human life and health and have been widely used in biology, chemistry, functional materials, etc. However, the high reactivity, disorder, and short half‐lives limit their wide applications. Therefore, it remains a great challenge to prepare stable and ordered radicals. Herein, radicals are prepared with protective umbrellas (diethylmethyleneamine, DEMA) that are integrated on the surface of 2D layered materials to isolate water and oxygen and enhance the stability of radicals. Taking 2D black phosphorus (BP) as an example: triethylamine reacts with dichloromethane to form quaternary ammonium salts with further Hoffmann elimination to produce DEMA radicals that could react with one electron of a lone pair electrons in P on the surface of BP to produce P radicals, which shows a prolonged half‐life of 21 days at room temperature. First‐principle calculations and electron paramagnetic resonance fitting confirm that the steric hindrance constructed by dense DEMA passivation layer acts as a protective umbrella and the 2D coupling of P radicals and other P atoms in 2D BP plane to enhance the stability and strong superexchange interaction of P radicals. Furthermore, it is a general strategy to produce stable radicals integrated on the 2D plane. Abstract : An on‐surface reaction strategy is developed to integrate radicals with protective umbrellas on 2D layered material surfaces to construct stable and ordered radicals. For example, triethylamine reacts with dichloromethane to form quaternary ammonium salts with further Hofmann elimination to produce diethylmethyleneamine (DEMA) radicals, reacting with black phosphorus (BP) to produce P radicals with DEMA protective umbrellas integrated on BP surface.